Arts and Science (2011)
The science writing workshop of EAFIT Children's University began in September this year with a group of five participants of Expeditions to Knowledge. In the first sessions, each one of them chose a question of their interest among those asked by the children in the Question Network, and we have been working to answer it through writing and research exercises.